The role of the nasal allergen provocation test in local allergic rhinitis cases: a preliminary report - Krzych-Fałta, Edyta (Postepy Dermatol Alergol, 2019)
INTRODUCTION: The current state of knowledge is that allergic rhinitis can occur in two forms. One is allergic rhinitis as a manifestation of a systemic allergy with systemic atopy and positive results of skin prick tests or sIgE tests. The other is local allergic rhinitis (LAR) as a local allergic reaction affecting only the nasal mucosa without systemic atopy. AIM: To attempt to assess the usefulness of the nasal allergen provocation test for the purposes of differential diagnosis and the qualification of LAR patients for therapy. MATERIAL AND METHODS: The subjects in the study were a group of 6 adults diagnosed with LAR on the basis of their medical history and the results of nasal allergen provocation tests, with the allergens being house dust mites (Dermatophagoides pteronyssinus, Dermatophagoides farinae). The methods adopted in the study were a point-based rating scale as a measure of nasal/extranasal complaints and active anterior rhinomanometry. RESULTS: Significant differences (p < 0.05) were observed, using the subjective rating scale, in relation to registered nasal and extranasal complaints in the early phase of the allergic reaction. Similarly, the rhinomanometry method revealed significant differences in nasal resistance values before and after the administration of an allergen. CONCLUSIONS: The nasal allergen provocation test is the only testing tool that objectively measures the degree of the patient’s allergic reactions and is useful in qualifying LAR patients for further therapy.